Enantioselective [3 + 2] annulation of α-substituted allenoates with β,γ-unsaturated N-sulfonylimines catalyzed by a bifunctional dipeptide phosphine - Ni H. (Beilstein-Institut, 2018)
10.3762/bjoc.12.37